Population-based evaluation of the effectiveness of two regimens for emergency contraception. Issue 3 (June 2016) - Leung, Vivian W.Y.; Soon, Judith A.; Lynd, Larry D.; Marra, Carlo A.; Levine, Marc
Abstract: Objective: To estimate and compare the effectiveness of the levonorgestrel and Yuzpe regimens for hormonal emergency contraception in routine clinical practice. Methods: A retrospective population-based study included women who accessed emergency contraceptives for immediate use prescribed by community pharmacists in British Columbia, Canada, between December 2000 and December 2002. Linked administrative healthcare data were used to discern the timings of menses, unprotected intercourse, and any pregnancy-related health services. A panel of experts evaluated the compatibility of observed pregnancies with the timing of events. The two regimens were compared with statistical adjustments for potential confounding. Results: Among 7493 women in the cohort, 4470 (59.7%) received levonorgestrel and 3023 (40.3%) the Yuzpe regimen. There were 99 (2.2%) compatible pregnancies in the levonorgestrel group and 94 (3.1%) in the Yuzpe group ( P = 0.017). The estimated odds ratio for levonorgestrel compared with the Yuzpe regimen after adjusting for potential confounders was 0.64 (95% confidence interval 0.47–0.87). Against an expected pregnancy rate of approximately 5%, the relative and absolute risk reductions were 56.0% and 2.8%, respectively, for levonorgestrel and 36.7% and 1.8% for the Yuzpe regimen. Conclusion: The levonorgestrel regimen is more effective than the Yuzpe regimen in routine use. The data suggest that both regimens are less effective than has been observed in randomized trials.